Point-of-care assessment of platelet reactivity in the emergency department may facilitate rapid rule-out of acute coronary syndromes: a prospective cohort pilot feasibility study. Issue 1 (17th January 2014) - Darling, Chad E; Sala Mercado, Javier A; Quiroga-Castro, Walter; Tecco, Gabriel F; Zelaya, Felix R; Conci, Eduardo C; Sala, Jose P; Smith, Craig S; Michelson, Alan D; Whittaker, Peter; Welch, Robert D; Przyklenk, Karin
Abstract : Objective: Accurate, efficient and cost-effective disposition of patients presenting to emergency departments (EDs) with symptoms suggestive of acute coronary syndromes (ACS) is a growing priority. Platelet activation is an early feature in the pathogenesis of ACS; thus, we sought to obtain an insight into whether point-of-care testing of platelet function: (1) may assist in the rule-out of ACS; (2) may provide additional predictive value in identifying patients with non-cardiac symptoms versus ACS-positive patients and (3) is logistically feasible in the ED. Design: Prospective cohort feasibility study. Setting: Two urban tertiary care sites, one located in the USA and the second in Argentina. Participants: 509 adult patients presenting with symptoms of ACS. Main outcome measures: Platelet reactivity was quantified using the Platelet Function Analyzer-100, with closure time (seconds required for blood, aspirated under high shear, to occlude a 150 µm aperture) serving as the primary endpoint. Closure times were categorised as 'normal' or 'prolonged', defined objectively as the 90th centile of the distribution for all participants enrolled in the study. Diagnosis of ACS was made using the standard criteria. The use of antiplatelet agents was not an exclusion criterion. Results: Closure times for the study population ranged from 47 to 300 s, with a 90th centile value of 138 s. The proportion of patients with closure times ≥138 s was significantly higher in patients with non-cardiac symptoms (41/330; 12.4%) versus the ACS-positive cohort (2/105 (1.9%); p=0.0006). The specificity of 'prolonged' closure times (≥138 s) for a diagnosis of non-cardiac symptoms was 98.1%, with a positive predictive value of 95.4%. Multivariate analysis revealed that the closure time provided incremental, independent predictive value in the rule-out of ACS. Conclusions: Point-of-care assessment of platelet reactivity is feasible in the ED and may facilitate the rapid rule-out of ACS in patients with prolonged closure times.